SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN DANA BANTUAN POSYANDU STUDI KASUS DESA CILEBUT BARAT KECAMATAN SUKARAJA KOTA BOGOR: Decision Support System for Posyandu Aid Funding Case Study of Cilebut Barat Village, Sukaraja District, Bogor City - Sefrika Sefrika (Institute of Computer Science (IOCS), 2019)
Integrated Family Planning and Health Service Post (Posyandu) is a basic health activity organized from, by and for communities assisted by health workers. Posyandu is a self-help activity from the community in the health sector. Posyandu starts primarily to serve toddlers consisting of immunization services, weighing, counseling and the elderly (Posyandu Lansia). But in its implementation, POSYANDU has problems with funding needs. Not all POSYANDUs get operational assistance from the local government. Particularly what happened in Cilebut Barat Village, Sukaraja Subdistrict, Bogor Regency, POSYANDU assistance has not been fully channeled to all targets. This is related to the absence of a decision support system that can assist village governments in providing POSYANDU funds. This study aims to determine what factors can be used as decision support systems that can be used by village governments in providing operational assistance to POSYANDU. The study used the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method which can be used to assist in decision making. The results of the study show that the decision support system with the TOPSIS method can be used by the Village Government to provide a decision to provide financial assistance to POSYANDU. The final Preference score resulted in 0.53 for the criteria for the Number of Active Participants (C3), Posyandu Has a Basic Health Service Program (C4) as an ideal criterion for providing financial assistance